Intelligent air-cushion tracked vehicle performance investigation: neural-networks - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Ramesh, Singh (Inderscience Enterprises Ltd., 2012)
The Intelligent Air-Cushion Tracked Vehicle (IACTV) is given focus as an alternative to conventional off-road vehicles, which are driven by track and air-cushion systems. To make the IACTV as effi cient as possible, proper investigation of the vehicle’s performance is essential. The most relevant factors that affect the competitive effi ciency of the (ACTV) are the Tractive Effort (TE), Motion Resistance (MR) and Power Consumption (PC). Therefore, an Artifi cial Neural-Network (ANN) model is proposed to investigate the vehicle’s performance. Cushion Clearance Height (CH), and Air-Cushion Pressure (CP)are used at the input layers, while PC, TE and MR are used at the output layers. Experiments are carried out in the fi eld to investigate the vehicle’s performance, and the fi ndings are compared with the results obtained from ANN.